Ganoderma lucidum: a comprehensive review of phytochemistry, efficacy, safety and clinical study - Sijia Wu; Siyuan Zhang; Bo Peng; Dechao Tan; Mingyue Wu; Jinchao Wei; Yitao Wang; Hua Luo (Food Science and Human Wellness)
Ganoderma lucidum, one of the most well-known edible fungi, is believed to be very benef icial for longevity and vitality. A long usage history suggests that G. lucidum has various clinical therapeutic effects. And experimental studies have confirmed that G. lucidum has multiple pharmacological effects, including antitumor, anti-microbial, anti-HIV protease, and antidiabetic activity and so on. With the deepening of research, more than 300 compounds have been isolated from G. lucidum. There is an increasing population of G. lucidum-based products, and its international development is expanding. Currently, G. lucidum has drawn much attention to its chemical composition, therapeutic effect, clinical value, and safety. This paper provides a comprehensive review of these aspects to enhance the global promotion of G. lucidum.